Study On The Experiment of Medium Carbon Steel Welded With Smaw and Quenched With Sea Water - Erizal .; Diah K Pratiwi (Universitas Sriwijaya, 2015)
Abstract. This research was conducted to find the effect of sea water cooling media on mechanical properties and physical properties of the medium carbon steel welded SMAW. Testing performed on two types of specimens were medium carbon steel welded and non-welded, quenching performed at temperatures of 850ºC, then tested the hardness, tensile strength and microstructure . The results of the study of media of sea water cooling on mechanical properties of carbon steel welded medium SMAW on tensile test is known. the average tensile ductility in the welded specimens is lower than that is not welded. In both specimens were quenched welded and non-welded experienced an average increase in tensile ductility . However, the average value of tensile ductility on welded specimens and quenched lower than that is not welded. In the hardness test show the increase of average of hardness against Vickers. Likewise welded specimens and quenched on average HAZ area hardness, whereas in the weld area is not quenched hardness higher than that is not welded. However, welded is lower the hardness quenched specimens quenched and not welded. Test results on the microstructure of specimens made quenching the metal HAZ area was clear and its martensite Ferrite grain boundaries and the area looks ferrite weld metal and its martensite dominant.